Listening to voice hearers. (November 2013) - Sapey, Bob; Bullimore, Peter
Summary: This article considers what the Hearing Voices Network can offer to mental health social work. It combines an extensive literature review of voice hearing by Bob Sapey and the expertise by experience of Peter Bullimore who runs a peer support group for voice hearers. Findings: The re-framing of auditory hallucinations as voice hearing has significantly changed the way many voice hearers have been able to understand their experience. This new approach to working with voices was developed at the University of Maastricht, principally by social psychiatrist Marius Romme. By moving away from biological explanations of brain disease to psychological understandings of emotions, Romme and his colleagues have found ways of helping people cope with voices, rather than trying to get rid of them through medication. This has led to a network of voice hearing groups throughout the world. There is much of what happens in these groups and within the social psychiatric responses known as the Maastricht approach that can be practiced by social workers. Applications: The Maastricht approach to working with voices challenges the basis of pharmacological responses to psychosis and moves beyond anti-psychiatry by offering positive alternatives to the current biomedical treatment of schizophrenia. This approach can be undertaken by experts by experience and mental health professionals. We describe these approaches and argue that in adopting them, social workers can help voice hearers cope both with the content of their voices and the stigmatising responses to being diagnosed with schizophrenia.